2018
DOI: 10.1016/j.childyouth.2018.09.011
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of attachment on the association between childhood maltreatment and adolescent dating violence

Abstract: Approximately twenty percent of female and ten percent of male adolescents report violence in their dating relationships and there is a significant association between dating violence in adolescence and later perpetration of intimate partner violence (IPV) in adulthood. Identification of factors associated with dating violence can inform intervention and prevention efforts. This study was designed to examine the associations of early childhood maltreatment experience and involvement in adolescent dating violen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 84 publications
(101 reference statements)
1
13
1
8
Order By: Relevance
“…In a study of undergraduate students between the ages of 18 and 25, attachment anxiety and attachment avoidance were not significant predictors of dating violence perpetration in men; however, in women, attachment anxiety, and not attachment avoidance, was predictive of dating violence perpetration [ 41 ]. In a third study in a predominately African American sample it was found that for those with a secure attachment pattern, their history of childhood maltreatment was not a significant risk factor of dating violence [ 42 ]. In addition, the same study found a moderating role of avoidant/dismissing attachment in the pathway from exposure to maltreatment in childhood to dating violence victimization [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of undergraduate students between the ages of 18 and 25, attachment anxiety and attachment avoidance were not significant predictors of dating violence perpetration in men; however, in women, attachment anxiety, and not attachment avoidance, was predictive of dating violence perpetration [ 41 ]. In a third study in a predominately African American sample it was found that for those with a secure attachment pattern, their history of childhood maltreatment was not a significant risk factor of dating violence [ 42 ]. In addition, the same study found a moderating role of avoidant/dismissing attachment in the pathway from exposure to maltreatment in childhood to dating violence victimization [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a third study in a predominately African American sample it was found that for those with a secure attachment pattern, their history of childhood maltreatment was not a significant risk factor of dating violence [ 42 ]. In addition, the same study found a moderating role of avoidant/dismissing attachment in the pathway from exposure to maltreatment in childhood to dating violence victimization [ 42 ]. Although not using an adolescent sample, a study by Babcock, Jacobson, Gottman, and Yerington (2000) found that dismissing husbands were more likely to perpetrate violence if the wife was defensive and preoccupied men were more likely to perpetrate violence if they noticed their wife’s withdrawal [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…En este orden de ideas, una fortaleza de esta investigación ha sido presentar a través de dos modelos los diferentes factores asociados con el maltrato y la victimización de la violencia en las relaciones de pareja en una muestra de adolescentes colombianos. Estos hallazgos se constitu-yen en un insumo para orientar procesos de prevención e intervención de este fenómeno en población adolescente (Stovera, Choib & Mayesa, 2018;Yu et al, 2018).…”
Section: Discussionunclassified
“…Finalmente, se ha identificado que los adolescentes con antecedentes de maltrato infantil y estilos de apego evitativo pueden tener un mayor riesgo de participación en violencia en el noviazgo (Stovera, Choib & Mayesa, 2018).…”
Section: Palabras Claveunclassified
“…Alternatively, the intergenerational transmission of violence may also be understood within the framework of attachment theory (Stover, Choi, & Mayes, 2018; Widom & Wilson, 2015). According to attachment theory, children form internal working models about themselves and others based on the quality of the parent–child relationship (Bowlby, 1977).…”
Section: Intergenerational Transmission Of Violencementioning
confidence: 99%